Model-driven development for embedded software : application to communications for drone swarm - Maxa, Jean-Aime; Ben Mahmoud, Mohamed Slim; Larrieu, Nicolas (ISTE Press Ltd, 2018)
Model-driven Development for Embedded Software: Application to Communications for Drone Swarm describes the principles of model-oriented design used in the aeronautical field, specifically for the UAV (Unmanned Aerial Vehicle). The book focuses on designing an embedded system for drones to carry out ad hoc communication within a drone fleet. In this context, an original methodology for rapid prototyping of embedded systems is presented. This approach saves time for the verification and formal validation phases, contributing to certification of the Unmanned Aerial System (UAS). The book also addresses the more traditional verification phases that must be performed to verify accuracy of the system. This evaluation is carried out in simulation and by real experimentation. The various tools necessary for the implementation of this methodology are described to allow the reader to be able to implement independently. Finally, to illustrate the contribution of this original methodology, an example of embedded system development is presented in which the different phases of the methodology are explained to conceive, validate and test a new secure routing protocol developed for communications within a fleet of drones.